Reaction network for the total oxidation of toluene over CuO–CeO2/Al2O3 - Menon, Unmesh; Galvita, Vladimir V.; Marin, Guy B. (Journal of catalysis, 2011)
Graphical abstract Alternating pulse and isotopic labeling experiments indicate that the catalytic total oxidation of toluene over CuO-CeO2 /γ-Al2 O3 consists of the following sequence: parallel adsorption of toluene on the catalyst surface, step 1; the simultaneous abstraction of H from the methyl and the phenyl group, steps 2 and 3; abstraction of the methyl carbon atom, step 4, followed by destruction of the aromatic ring, step 5. Two types of oxygen are directly involved in the oxidation of toluene: adsorbed oxygen and weakly bound surface lattice oxygen. Display Omitted Highlights Reaction network for the total oxidation of toluene over CuO-CeO2 /Al2 O3 . Transient response techniques with millisecond time scale. The role and nature of the respective oxygen active species. Life time of the reactants species on the catalyst surface. Isotopic labeling experiments with 18 O2 , C6 H5 -13 CH3 , and C6 H5 -CD3 . The total oxidation of toluene was studied over a CuO-CeO2 /γ-Al2 O3 catalyst in a Temporal Analysis of Products (TAP) setup in the temperature range 673-923K in the presence and absence of dioxygen and at various degrees of reduction of the catalyst. The reaction rate significantly decreases over a mildly reduced catalyst. Under vacuum and at high-temperature, mild reduction also occurs in the absence of toluene. In the presence of dioxygen, the catalyst activity is determined by weakly bound surface lattice oxygen atoms and adsorbed oxygen species, the lifetime of which is close to 1s. The weakly bound oxygen is highly reactive and is only found over a fully oxidized catalyst. The formation of products containing 18 O during the isotope-exchange experiments with 18 O2 indicates that both lattice and adsorbed oxygen are involved in (a) reoxidation of mildly reduced copper oxide and (b) abstraction of hydrogen atoms and scission of C-C bonds. Isotopic labeling with C6 H5 -13 CH3 and C6 H5 -CD3 indicates the following reaction paths: adsorption of toluene on the active site, containing Cu2+ with 4-5 adjacent surface lattice oxygen atoms; the simultaneous abstraction of H from the methyl and the phenyl group followed by the abstraction of the methyl carbon and next the destruction of the aromatic ring. [PUBLICATION ABSTRACT]